2012
DOI: 10.1007/s00264-012-1644-0
|View full text |Cite
|
Sign up to set email alerts
|

Balloon osteoplasty—a new technique for minimally invasive reduction and stabilisation of Hill–Sachs lesions of the humeral head: a cadaver study

Abstract: Purpose Traumatic shoulder dislocation may be complicated by concomitant bony injury of the glenoid rim or the humeral head. In Hill-Sachs lesions, reconstruction techniques vary widely and range from open reduction to tendon transposition or humeral head derotation. These operations are extensive and have questionable outcomes. With the expertise from vertebral compression fracture reduction by kyphoplasty, we examined in a cadaver feasibility study whether reduction of the Hill-Sachs lesion via hydraulic lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Kazel et al 11 were the first authors to coin the term "humeroplasty," when they created Hill-Sachs lesions in 14 cadaveric specimens and then used a curved bone tamp to significantly reduce the size of the lesions. Sandmann et al 12 advanced the technique further and used a kyphoplasty balloon to reduce the size of a HillSachs lesion. They used 6 cadaveric specimens for their study and showed that a balloon kyphoplasty system could reduce the size of a Hill-Sachs lesion by 80%, but they noted that further studies needed to be performed to evaluate the technique under arthroscopic conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kazel et al 11 were the first authors to coin the term "humeroplasty," when they created Hill-Sachs lesions in 14 cadaveric specimens and then used a curved bone tamp to significantly reduce the size of the lesions. Sandmann et al 12 advanced the technique further and used a kyphoplasty balloon to reduce the size of a HillSachs lesion. They used 6 cadaveric specimens for their study and showed that a balloon kyphoplasty system could reduce the size of a Hill-Sachs lesion by 80%, but they noted that further studies needed to be performed to evaluate the technique under arthroscopic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Sandmann et al 12 described the use of a kyphoplasty balloon with subsequent filling of the defect with bone substitute (similar to the fixation of a vertebral compression fracture), which they performed on cadaveric specimens. Stachowicz et al 13 described the same technique used on cadavers.…”
mentioning
confidence: 99%
“…They also target limited geometries, as they very often rely on inflatable balloons for deployment [6,7]. Adapting these device designs for planar configurations while at the same time providing the ability to incorporate electrical, optoelectronic and other sensing and actuation capabilities are highly desirable to further expand the usage of deployable devices and to facilitate the exploration of novel applications.…”
Section: Open Accessmentioning
confidence: 99%
“…Dear Editor, We have read the article "Balloon osteoplasty-a new technique for minimally invasive reduction and stabilisation of Hill-Sachs lesions of the humeral head: a cadaver study" by Sandmann et al [1] with great interest.…”
mentioning
confidence: 99%